Project on Human Development in Chicago Neighborhoods (PHDCN): Child Behavior Checklist, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2006)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One of the measures that composed the Longitudinal Cohort Study was the Child Behavior Checklist (CBCL). The CBCL protocol, administered to parents or primary caregivers, was first developed by Thomas M. Achenbach and has been one of the most widely used standardized measures in child psychology for evaluating maladaptive behavioral and emotional problems in preschool subjects aged 2 to 3 or in subjects between the ages of 4 and 18. The CBCL was administered to primary caregivers of subjects belonging to Cohorts 0, 3, 6, 9, and 12 of the Longitudinal Cohort Study. It assessed internalizing (i.e., anxious, depressive, and overcontrolled) and externalizing (i.e., aggressive, hyperactive, noncompliant, and undercontrolled) behaviors. Several subareas were measured including social withdrawal, somatic complaints, anxiety and depression, social problems, thought problems, attention problems, aggressive behavior, and delinquent behaviors. The Wave 3 version of the instrument is nearly identical to the Wave 2 version, which was administered to Cohorts 3, 6, 9, 12, and 15 (PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): CHILD BEHAVIOR CHECKLIST, WAVE 2, 1997-2000 [ICPSR 13611]). The Wave 3 version contains a question regarding cruelty to animals that was not present in the Wave 2 version for Cohorts 3, 6, 9, 12, and 15.